The Rise and Fall of the Victorian Three-Volume Novel. - Houston, Natalie M. (Victorian Studies)
"The Rise and Fall of the Victorian Three-Volume Novel" by Troy J. Bassett is a comprehensive study that challenges existing knowledge about multivolume fiction in the Victorian era. Bassett's research database, At the Circulating Library (ATCL), provides extensive bibliographic data on Victorian fiction, including information on novels, authors, and publishers. The book analyzes publishing data on 7,272 multivolume works of fiction published between 1837 and 1898, revealing a gradual increase in the number of novels published in this format until its decline in the late 19th century. The study also explores the economic structures and publishing systems that made multivolume fiction profitable for publishers, libraries, and authors. Overall, this book offers valuable insights into the Victorian novel and its relationship to publishing structures and formats.